2023
DOI: 10.3390/rs15112761
|View full text |Cite
|
Sign up to set email alerts
|

Improving Crop Mapping by Using Bidirectional Reflectance Distribution Function (BRDF) Signatures with Google Earth Engine

Abstract: Recent studies have demonstrated the potential of using bidirectional reflectance distribution function (BRDF) signatures captured by multi-angle observation data to enhance land cover classification and retrieve vegetation architectures. Considering the diversity of crop architectures, we proposed that crop mapping precision may be enhanced by using BRDF signatures. We compared the accuracy of four supervised machine learning classifiers provided by the Google Earth Engine (GEE), namely random forest (RF), cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Thus, it has been shown that the use of fitting functions to reconstruct NDVI time series and subsequent GB machine learning make it possible to perform crop mapping based on multi-year data. The high accuracy and productivity of the proposed method determine the prospects for its use in regions with similar cropland structures and crop phenological cycles, including the developing agricultural regions of Northeast China that have large areas of cropland [3,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that the use of fitting functions to reconstruct NDVI time series and subsequent GB machine learning make it possible to perform crop mapping based on multi-year data. The high accuracy and productivity of the proposed method determine the prospects for its use in regions with similar cropland structures and crop phenological cycles, including the developing agricultural regions of Northeast China that have large areas of cropland [3,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…They explained that the classifiers were ranked according to accuracy, from highest to lowest: RF, CART, SVM, and NB. Finally, they concluded that this study contributes to the development of crop area mapping and the application of multi-angle monitoring satellites [3]. The application of machine learning technology using RF to classify Landsat satellite images in the mountainous terrain of the Himalayas in the western side of the Indian state was presented.…”
Section: Introductionmentioning
confidence: 89%
“…The Bidirectional Reflectance Distribution Function (BRDF) is defined as the ratio of the irradiance in a given outgoing direction to the irradiance in a given incoming direction on that surface element, and this function can be used to characterize the surface reflectance anisotropy [1,2]. Currently, it is mainly applied to radiometric correction of satellite-borne instruments [1], radiometric correction of low-altitude images [3], light utilization, albedo inversion [4,5], crop mapping [6], crop element estimation [7], and estimation of metal surface roughness [8]. The modeling accuracy of the BRDF has directly impacted the application of quantitative remote sensing.…”
Section: Introductionmentioning
confidence: 99%